Perlindungan Hukum Terhadap Pasar Tradisional Dari Keberadaan Pasar Modern di Kabupaten Jembrana - Dewi, Cokorde Istri Dian Laksmi; Dharma, Ida Bagus Wirya (Universitas Tabanan, 2023)
Jembrana Regency has 26 modern shopping centers spread across five districts. The rapid development of the trading business in the form of modern shops has created new problems for small traders and traders in traditional markets. This study examines how the existence of traditional markets amid the rise of modern markets in Jembrana district, and how legal protection efforts are provided by the Jembrana district government for traditional markets. The legal research method used in this paper is empirical legal research, which focuses on phenomena in people's lives. The results of the study found that there were more modern markets than traditional markets, based on this the Jembrana Regency Government issued Regional Regulation of Jembrana Regency Number 8 of 2010 concerning Arrangement and Empowerment of Traditional Markets, Shopping Centers and Modern Shops. This Regency Regional Regulation aims that economic development between traditional markets and modern markets can jointly develop the Jembrana Regency economy in a balanced manner.